Epidemiology of pyogenic liver abscesses in Germany: Analysis of incidence, risk factors and mortality rate based on routine data from statutory health insurance. Issue 9 (30th July 2021) - Zimmermann, Lisa; Wendt, Sebastian; Lübbert, Christoph; Karlas, Thomas
Abstract: Background: Pyogenic liver abscesses (PLAs) represent potentially life‐threatening abdominal conditions that require immediate diagnosis and therapy. European and American incidence figures vary between one and 15 per 100, 000 per year. Structured epidemiological data for European countries are not available. Objective: To systematically characterize the epidemiology and clinical outcome of PLA in Germany. Methods: In representative statutory health insurance data from four million people in 2013–2019, the prevalence and incidence with clinical coding of International Statistical Classification of Diseases and Related Health Problems (ICD)‐10 code K75.0 were selected ( n  = 1118). Furthermore, demographics, relevant comorbidities, hospitalizations, mortality and complications were determined within one year. Results: The incidence of PLA was approximately seven per 100, 000. The average age at diagnosis was 66 years; 65% were male. Of these, biliary disease was documented in over 60% and infectious intestinal diseases were found in 21% within the same or previous calendar year. PLA patients had high comorbidity indices. Liver transplant status, malignancies of the liver and biliary system, liver cirrhosis and pancreatitis were strongly associated. Intensive care was documented in 27% of PLA cases. Nine percent died within 12 months, most with an underlying malignant disease. Conclusion: Pyogenic liver abscess is a rare disease with high morbidity. Predisposing and risk factors include intestinal and biliary diseases as well as hepatic malignancies. Further research should focus on PLA therapy within prospective surveys and controlled clinical trials.